Intrinsic and Extrinsic Learning Motivation of Elementary School Students: A Descriptive and Empirical Analysis - Musfirah, Musfirah; Imron Burhan; Amriadi, Amriadi (Cita konsultindo, 2025)
This study aims to explore the learning motivation of elementary school students, focusing on intrinsic and extrinsic motivation. Intrinsic motivation refers to the internal drive that comes from the students’ desire to achieve personal goals and feel satisfied with their academic achievements, while extrinsic motivation is influenced by external factors such as support from parents, teachers, and rewards received. A survey involving 15 respondents was conducted, and descriptive statistical analysis was used to illustrate the frequency distribution of students’ motivation levels. The study found that most students have strong intrinsic motivation, as reflected in their scheduled study habits, efforts to achieve good grades, and satisfaction with their academic accomplishments. On the other hand, extrinsic motivation, which comes from parental support and teacher rewards, also proves to be effective in increasing students' enthusiasm and study habits. Although there were differences in the level of agreement regarding the influence of parental advice on poor grades, overall, these external factors strengthened students’ motivation to achieve their academic targets. This study concludes that the development of both intrinsic and extrinsic motivation simultaneously can be an effective strategy for improving students' academic performance.